Cardiovascular complications in patients with severe pneumonia with influenza A/H1N1 / 09 - Yu. V. Pervoushina; V. V. Gorbunov; S. A. Lukyanov (Сибирский научный медицинский журнал, 2021)
Aim of the study was to analyze the frequency and nature of cardiovascular complications in influenza A/H1N1/09 in Zabaykalsky Krai from 2018 to 2019. Material and methods. 86 cases of severe influenza A/H1N1/09 were analyzed. Results. The patients were divided into 2 groups, comparable by gender and age. The first group consisted of patients with cardiovascular complications of influenza A/H1N1 / 09 (41 people). The second group consisted of patients without complicated flu (45 people). The average age of patients in the first group was 60 ± 13.7 years. According to the ECG results, sinus tachycardia with a heart rate of 94 ± 14.2 beats/min was dominant, in combination with various rhythm and conduction disorders: supraventricular extrasystole – in 5 (12 %) patients, acute (paroxysmal) atrial fibrillation – in 19 (46 %), ventricular extrasystole – in 7 (17 %), complete right and left bundle branch block – in 7 (17 %) and 7 (17 %), respectively, atrioventricular block of the 1st degree – in 1 (2 %) patients. Long QT syndrome was revealed in 5 patients (12 %). The severe cardiovascular system complications were: myopericarditis in 2 (5 %) people, decompensation of chronic heart failure in 4 (10 %) people, pulmonary embolism in 1 (2 %), acute myocardial infarction in 11 (27 %). The mortality rate in this group was 12 (29 %) cases from hospitalized patients. The average age of patients in the second group was 58 ± 14.1 years. According to the ECG results, sinus tachycardia with a heart rate of 91 ± 9.4 beats/min was detected in 98 % of cases, 3 (7 %) patients had complete left bundle branch block, 1 (2 %) patient had atrial fibrillation. No other rhythm or conduction disturbances were detected. No organic heart pathology was detected in this group of patients. The mortality rate was 5 (11 %) people. Conclusion. The analysis of 86 cases showed that elderly patients with a heavy premorbid background prevailed. The severe cardiovascular system complications were mainly represented by cardiac arrhythmias and the development of acute myocardial infarction. The fatal outcome occurred on the 8th-22nd day from the onset of the disease. The presence of cardiovascular complications doubles the mortality rate.